WA Newspaper's contempt finding - Fernandez, Joseph (Law Society of WA, 2005)
In July 2004, Western Australia's largest circulating daily newspaper, The West Australian, identified a nine-year-old ward of the State, thereby breaching a statutory provision. It described him as a "suburban terrorist" and a "menace to society". A year later the Supreme Court of Western Australia reminded the media that such coverage can also be a menace to society and imposed $20,000 in fines for contempt of court. In this article the author surveys contempt law from a media perspective and considers the case in question.